Counting Young Carers in Switzerland – A Study of Prevalence. (2nd November 2018) - Leu, Agnes; Frech, Marianne; Wepf, Hannah; Sempik, Joe; Joseph, Stephen; Helbling, Laura; Moser, Urs; Becker, Saul; Jung, Corinna
Abstract : An online survey of children in school grades 4–9 (mostly aged 10–15) was conducted in order to determine the prevalence of young carers in Switzerland using a 2‐stage stratified sampling approach. 4082 respondents were drawn from 230 schools. A total of 3991 respondents were included in the analysis and of these 307 (7.7%) were identified as young carers. The population estimate of prevalence was 7.9 per cent. This suggests that there are around 38 400 young carers in school grades 4–9 in Switzerland. Extrapolating to the 9–16 age group gives a figure of almost 51 500.